Active material, electrode, secondary battery, battery pack, and vehicle

Niobium-containing oxides with controlled particle structures address the limitations of titanium oxides by enhancing lithium ion diffusion and conductivity, resulting in secondary batteries with improved energy density and stability for rapid charging and discharging.

JP2025016162APending Publication Date: 2025-01-31KK TOSHIBA
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023119262
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-21
Publication Date
2025-01-31

AI Technical Summary

Technical Problem

Existing secondary batteries face challenges in achieving high energy density, rapid charging and discharging capabilities, and long-term reliability due to issues with lithium ion movement in electrodes, particularly with titanium oxides, which have low capacity per weight and high potential, leading to instability and reduced energy density.

Method used

The use of niobium-containing oxides with specific particle structures, including secondary particles with adjacent and necking parts between primary particles, enhances lithium ion diffusion and conductivity, stabilizing rapid charging and discharging while maintaining high energy density.

Benefits of technology

The niobium-containing oxide particles with controlled necking ratios and particle sizes improve lithium ion conductivity and electronic conductivity, enabling stable and efficient rapid charging and discharging with enhanced energy density and prolonged battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025016162000001_ABST
    Figure 2025016162000001_ABST
Patent Text Reader

Abstract

To provide an active material, capable of realizing a secondary battery of which the output performance is improved and which is capable of presenting a satisfactory lifetime performance, an electrode, the secondary battery of which the output performance is improved and which is capable of presenting the satisfactory lifetime performance, a battery pack, and a vehicle with the battery pack.SOLUTION: Provided is an active material containing a secondary particle including a plurality of primary particles each containing a niobium containing oxide. The secondary particle includes an adjacent portion, in which the primary particles are adjacent to each other, and a necking portion which is configured by bonding the primary particles with each other. A total peripheral length L of the primary particle and a total sum Lcl of the peripheral lengths of the primary particles excluding the necking portion satisfy a relation of 0.1<(L-Lcl) / L≤0.6.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] FIELD OF THE DISCLOSURE Embodiments of the present invention relate to an active material, an electrode, a secondary battery, a battery pack, and a vehicle. [Background technology]

[0002] In recent years, research and development of secondary batteries such as non-aqueous electrolyte secondary batteries, such as lithium ion secondary batteries, as high energy density batteries, has been actively promoted. Secondary batteries such as non-aqueous electrolyte secondary batteries are expected to be used as power sources for vehicles such as hybrid electric vehicles and electric vehicles, and for uninterruptible power sources for mobile phone base stations. Therefore, in addition to high energy density, secondary batteries are also required to have excellent other performances such as rapid charge and discharge performance and long-term reliability. For example, secondary batteries capable of rapid charge and discharge not only significantly reduce charging time, but also improve the power performance of vehicles such as hybrid electric vehicles and efficiently recover regenerative energy from power.

[0003] In order to enable rapid charging and discharging, it is necessary that electrons and lithium ions can move quickly between the positive and negative electrodes. However, when a battery using a carbon-based negative electrode is repeatedly charged and discharged rapidly, dendrites of metallic lithium are precipitated on the electrode, which may cause heat generation or fire due to an internal short circuit.

[0004] Therefore, batteries that use metal composite oxides instead of carbonaceous materials for the anode have been developed. Among them, batteries that use titanium oxide for the anode are capable of stable rapid charging and discharging and have a longer life than batteries that use carbon-based anodes.

[0005] However, titanium oxide has a higher potential relative to metallic lithium than carbonaceous materials, i.e., it is more noble. Moreover, titanium oxide has a low capacity per weight. Therefore, batteries using titanium oxide in the negative electrode have a problem of low energy density.

[0006] For example, the electrode potential of titanium oxide is about 1.5 V (vs. Li / Li) based on metallic lithium.+ ), which is higher (more noble) than the potential of a carbon-based negative electrode. The potential of titanium oxide is the potential of Ti when electrochemically inserting and extracting lithium. 3+ and Ti 4+ The charge is electrochemically limited because it is caused by an oxidation-reduction reaction between the two. + It is also true that rapid charging and discharging of lithium ions can be performed stably at high electrode potentials of about 1000 kV. Therefore, it is difficult to lower the electrode potential in order to improve the energy density.

[0007] On the other hand, in terms of capacity per unit weight, the theoretical capacity of titanium dioxide (anatase structure) is about 165 mAh / g, and Li4Ti5O 12 The theoretical capacity of spinel-type lithium-titanium composite oxides such as those shown in Fig. 1 is about 180 mAh / g. On the other hand, the theoretical capacity of general graphite-based electrode materials is 385 mAh / g or more. Thus, the capacity density of titanium oxides is significantly lower than that of carbon-based negative electrodes. This is because the crystal structure of titanium oxides has few sites for absorbing lithium and lithium is easily stabilized in the structure, resulting in a decrease in the actual capacity.

[0008] In view of the above, new electrode materials containing Ti and Nb are being considered. Niobium titanium oxide is expected to have high charge / discharge capacity. For example, an oxide represented by TiNb2O7 has a high theoretical capacity of over 380mAh / g. However, since the electronic conductivity of niobium titanium oxide is low, it does not have excellent output performance. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2019-57371 A [Patent Document 2] JP 2022-169210 A [Non-patent literature]

[0010] [Non-Patent Document 1] M.Gasperin, Journal of Solid State Chemistry 53, pp144-147 (1984) [Non-Patent Document 2] Dr. Michael et al., Image Processing with ImageJ, Reprinted from the July 2004 issue of Biophotonics International copyrighted by Laurin Publishing Co. INC. [Non-Patent Document 3] Izumi Nakai and Fujio Izumi (eds.), "Practical aspects of powder X-ray analysis," edited by the X-ray analysis research roundtable of the Japan Society for Analytical Chemistry, pp. 97-115, Asakura Publishing, published July 10, 2009 Summary of the Invention [Problem to be solved by the invention]

[0011] The object is to provide an active material and electrodes capable of realizing a secondary battery capable of exhibiting high output performance and excellent life performance, a secondary battery and battery pack capable of exhibiting high output performance and excellent life performance, and a vehicle equipped with this battery pack. [Means for solving the problem]

[0012] According to an embodiment, an active material is provided that includes secondary particles that include a plurality of primary particles that include a niobium-containing oxide. The secondary particles include adjacent portions where the primary particles are adjacent to each other and necked portions where the primary particles are joined to each other. The total perimeter L of the primary particles and the sum of the perimeters of the primary particles excluding the necked portions L cl That is, 0.1<(LL cl ) / L≦0.6.

[0013] According to another embodiment, an electrode is provided that includes the active material described above.

[0014] According to another embodiment, a secondary battery is provided that includes a positive electrode, a negative electrode including a negative electrode active material, and an electrolyte. The negative electrode active material includes secondary particles including a plurality of primary particles including a niobium-containing oxide. The secondary particles include a first adjacent portion where the primary particles are adjacent to each other, and a second adjacent portion where the primary particles are in contact with each other via an interface. The total perimeter L of the primary particles and the sum of the perimeters of the primary particles excluding the second adjacent portion L are cl That is, 0.1≦(LL cl ) / L≦0.6.

[0015] According to another embodiment, there is provided a battery pack including the above-described secondary battery.

[0016] According to another embodiment, a vehicle equipped with the above-described battery pack is provided. [Brief description of the drawings]

[0017] [Figure 1] FIG. 2 is a cross-sectional view that illustrates a secondary particle included in an example of an active material according to an embodiment. [Diagram 2] FIG. 1 is a cross-sectional view that illustrates an example of a conventional secondary particle of an active material. [Diagram 3] 1 is a cross-sectional scanning electron microscope image of an example of an electrode including an active material according to an embodiment. [Figure 4] The electron microscope image shown in Figure 3 was binarized and processed using erode processing. [Diagram 5] The electron microscope image shown in Figure 3 was binarized and subjected to closing processing. [Figure 6] FIG. 1 is a cross-sectional view illustrating an example of a secondary battery according to an embodiment. [Figure 7] FIG. 7 is an enlarged cross-sectional view of a portion A of the secondary battery shown in FIG. 6. [Figure 8] FIG. 4 is a partially cutaway perspective view illustrating a schematic diagram of another example of a secondary battery according to an embodiment. [Figure 9] 9 is an enlarged cross-sectional view of part B of the secondary battery shown in FIG. 8. [Figure 10] FIG. 1 is a perspective view illustrating an example of a battery pack according to an embodiment. [Figure 11]FIG. 1 is an exploded perspective view illustrating an example of a battery pack according to an embodiment. [Figure 12] 12 is a block diagram showing an example of an electric circuit of the battery pack shown in FIG. 11. [Figure 13] 1 is a partially see-through view illustrating an example of a vehicle according to an embodiment. [Figure 14] 1 is a diagram illustrating an example of a control system for an electrical system in a vehicle according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The inventors have found through a hybrid pulse power characteristic (HPPC) test that the active material particle size has a large effect on the overvoltage at the solid-liquid interface and the lithium (Li) concentration polarization inside the active material, which account for most of the battery resistance in a battery using niobium titanium oxide. Even when the particle size distribution of niobium titanium oxide particles is normal, the increase in resistance due to the active material having a large particle size is significant. In particular, when the particle size distribution is broad, coarse particles are included, and the increase in resistance due to these coarse particles is more significant.

[0019] Hereinafter, the embodiments will be described with reference to the drawings. Note that the same reference numerals are used to designate common components throughout the embodiments, and duplicated descriptions will be omitted. Each figure is a schematic diagram for explaining the embodiments and for facilitating understanding thereof, and the shapes, dimensions, ratios, etc. may differ from those of the actual device, but these can be appropriately modified in design by taking into consideration the following explanation and known techniques.

[0020] (First embodiment) According to a first embodiment, an active material is provided. The active material includes secondary particles containing a niobium-containing oxide. The secondary particles include a plurality of primary particles. The secondary particles include adjacent portions where the primary particles are adjacent to each other and necked portions where the primary particles are joined to each other. The total perimeter L of the primary particles and the sum of the perimeters of the primary particles excluding the necked portions L cl That is, 0.1<(LL cl ) / L≦0.6.

[0021] The necking portion in the active material corresponds to the grain boundaries between the primary particles that have higher Li diffusivity than the bulk. By having the necking portion, the active material can exhibit high Li diffusivity.

[0022] A cross-sectional view schematically showing secondary particles included in an example of the active material according to FIG. 1 is shown. The illustrated secondary particle 12 includes a plurality of primary particles 11, and some of the primary particles 11 are joined to form a necking portion 13. Due to the presence of the necking portion 13, the Li conductivity and the electron conductivity between the primary particles 11 are maintained. Since the primary particle 11 is an active material particle containing a niobium-containing oxide, it expands and contracts with the charge and discharge of the electrode containing the active material. As a result, although the necking portion 13 cracks, the primary particles 11 that constituted the necking portion 13 do not become independent of each other.

[0023] The necking ratio N indicating the degree of necking by the primary particles 11 in the active material is defined as the total perimeter L of the primary particles 11 and the sum of the perimeters of the primary particles 11 excluding the necking portion 13, L cl in relation to (L - L cl ), and is expressed as (L - L cl ) / L (that is, N = (L - L cl ) / L). Although details will be described later, the relationship (L - L cl ) / L representing the necking ratio N is obtained for an observation field including 100 or more primary particles 11. In an active material where the necking structure of the primary particles 11 in the secondary particle 12 satisfies the relationship 0.1 < (L - L cl ) / L ≤ 0.6 (0.1 < N ≤ 0.6), the Li conductivity is hardly impaired. Also, in an electrode containing such an active material, the overvoltage during charge and discharge at a high rate is low. The preferable range of (L - L cl ) / L is 0.2 or more and 0.6 or less, and more preferably 0.4 or more and 0.5 or less.

[0024] Conventional attempts to increase electrode capacity include reducing particle size and increasing electrode density. If the density of the electrode is increased while the particle size is small, the primary particles may become compacted as a result of expansion and contraction during charging and discharging. When fine primary particles become compacted within the electrode, isolated particles tend to form in the center of the secondary particles. The Li-conductivity and electronic conductivity between the isolated particles and other surrounding primary particles becomes low, impairing input / output performance and effectively reducing energy density.

[0025] An example is shown in Figure 2. The secondary particle 12 shown in the figure contains multiple primary particles 11, but there is no necking between the primary particles 11. Furthermore, the center of the secondary particle 12 contains an isolated particle 14, which is a primary particle isolated from the other primary particles 11. A gap is generated between the isolated particle 14 and the other primary particles 11 around it, and the resistance between the isolated particle 14 and the primary particles 11 is large.

[0026] An example of the niobium-containing oxide is a niobium titanium composite oxide. An example of the niobium titanium composite oxide is Nb2TiO7. The niobium-containing oxide is not limited thereto, but it is preferable that the niobium-containing oxide has a symmetry of the space group C2 / m and at least a part of the crystal structure has the atomic coordinates described in Non-Patent Document 1.

[0027] Niobium-containing oxides mainly exhibit a monoclinic crystal structure. For example, in the crystal structure of monoclinic Nb2TiO7, when lithium ions are inserted, the metal ions constituting the framework of the crystal structure are reduced to trivalent, thereby maintaining the electrical neutrality of the crystal. In niobium titanium oxide, not only are Ti ions reduced from tetravalent to trivalent, but Nb ions are reduced from pentavalent to trivalent. For this reason, the reduction valence per weight of active material is large. Therefore, even if many lithium ions are inserted, it is possible to maintain the electrical neutrality of the crystal. For this reason, the energy density is higher than that of compounds such as titanium oxide that contain only tetravalent cations. Niobium-containing oxides also have a low energy density of 1.5 V (vs. Li / Li +Therefore, an electrode containing a niobium-containing oxide as an active material can realize a battery capable of stable repeated rapid charging and discharging.

[0028] The niobium-containing oxide may be niobium titanium oxide. Niobium titanium oxide is, for example, Nb2TiO7, Nb2Ti2O9, Nb 10 Ti2O 29 , Nb 14 TiO 37 and Nb 24 TiO 62 The niobium titanium oxide may contain at least one crystal phase selected from the group consisting of: The niobium titanium oxide may be a substituted niobium titanium oxide in which at least a part of Nb and / or Ti is substituted with a different element. Examples of the substituted element include Na, K, Ca, Co, Ni, Si, P, V, Cr, Mo, Ta, Zr, Mn, Fe, Mg, B, Pb, and Al. The substituted niobium titanium oxide may contain one type of substituted element, or may contain two or more types of substituted elements. The active material particles may contain one type of niobium titanium oxide, or may contain multiple types of niobium titanium oxide. The niobium titanium oxide preferably contains monoclinic niobium titanium oxide Nb2TiO7. In this case, as described above, an electrode having excellent capacity and rate performance can be obtained.

[0029] An example of monoclinic niobium titanium oxide is Li x Ti 1-y M1 y Nb 2-z M2 z O 7+δ Here, M1 is at least one selected from the group consisting of Zr, Si, and Sn. M2 is at least one selected from the group consisting of V, Ta, and Bi. The subscripts in the composition formula are 0≦x≦5, 0≦y<1, 0≦z<2, and -0.3≦δ≦0.3.

[0030] Another example of monoclinic niobium titanium oxide is Ti 1-y M3 y+z Nb 2-z O7-δ Here, M3 is at least one selected from Mg, Fe, Ni, Co, W, Ta, and Mo. The subscripts in the composition formula are 0≦y<1, 0≦z<2, and -0.3≦δ≦0.3.

[0031] The active material may be only particles containing niobium-containing oxide, or may contain active materials other than particles containing niobium-containing oxide. The content of the particles containing niobium-containing oxide in the active material is preferably in the range of 75% by weight or more and 100% by weight or less. The content of the particles containing niobium-containing oxide in the active material is preferably closer to 100% by weight.

[0032] As an active material (second active material) other than the niobium-containing oxide, for example, lithium titanate having a ramsdellite structure (e.g., Li 2+y Ti3O7, 0≦y≦3), lithium titanates with spinel structure (e.g., Li 4+x Ti5O 12 , 0≦x≦3), monoclinic titanium dioxide (TiO2(B)), anatase titanium dioxide, rutile titanium dioxide, hollandite titanium composite oxide, and orthorhombic titanium-containing composite oxide.

[0033] As an example of the above-mentioned orthorhombic titanium-containing composite oxide, Li 2+a M I 2-b Ti 6-c M II d O 14+σ In this case, the compound represented by M I is at least one selected from the group consisting of Sr, Ba, Ca, Mg, Na, Cs, Rb and K. II is at least one selected from the group consisting of Zr, Sn, V, Nb, Ta, Mo, W, Y, Fe, Co, Cr, Mn, Ni, and Al. The subscripts in the composition formula are 0≦a≦6, 0≦b<2, 0≦c<6, 0≦d<6, and -0.5≦σ≦0.5. Specific examples of orthorhombic titanium-containing composite oxides include Li 2+aNa2Ti6O 14 (0≦a≦6).

[0034] The average particle size of the primary particles containing the niobium-containing oxide is preferably in the range of 0.5 μm to 3 μm, more preferably in the range of 0.5 μm to 2 μm. By making the average particle size 0.5 μm or more, the electrode density can be increased to improve the contact between the active material particles in the electrode and the contact between the active material particles and the conductive agent, thereby improving the life performance. In addition, the reaction between the particles containing the niobium-containing oxide and the electrolyte can be suppressed, so that the rapid charge / discharge performance can be improved. In addition, by making the average particle size 3 μm or less, the Li ion diffusion distance in the solid can be made appropriate, and the rapid charge / discharge performance can be improved. The method for measuring the average particle size will be described later.

[0035] The crystallite size of the particles containing the niobium-containing oxide is, for example, in the range of 10 nm to 300 nm, preferably in the range of 50 nm to 200 nm, and more preferably in the range of 80 nm to 120 nm. When the crystallite size is within this range, Li ion conduction in the crystal proceeds smoothly, thereby improving the charge / discharge efficiency and rate performance.

[0036] <Manufacturing method> Such an active material can be produced by the following method.

[0037] First, the starting materials are mixed. As an example of a niobium-containing oxide, an oxide or salt containing Li, Ti, and Nb is used as a starting material for niobium titanium oxide. The salt used as the starting material is preferably a salt that decomposes at a relatively low temperature to produce an oxide, such as a carbonate or a nitrate. The particle size of these starting materials is preferably in the range of 0.1 μm to 10 μm, more preferably in the range of 0.1 μm to 5 μm. This is because if it is smaller than 0.1 μm, it is likely to float in the air during mixing, causing composition deviation, and if it is larger than 10 μm, unreacted products are generated.

[0038] In addition to the above starting materials containing the constituent elements of the oxide, a material containing at least S is further mixed to form a flux. As a material containing S that can be used in the flux, for example, sulfates such as sodium sulfate can be used. In addition to the material containing S, a material containing P or a material containing K may also be used in the flux.

[0039] When mixing the starting materials, they are mixed in a molar ratio such that the Nb source and Ti source have the target composition. The flux material is mixed in an amount such that the molar ratio of each of S, P, and K to Nb is 1 or less. The mixed materials are pre-fired at a temperature in the range of 500°C to 1000°C for about 2 to 5 hours. The powder after pre-fired is pulverized in a ball mill for 1 hour and then subjected to main firing. The main firing is performed at a temperature of 1000°C to 1450°C in two or more separate firings for a total of 10 to 40 hours.

[0040] After the main firing, the obtained powder is subjected to a pulverization process. In the pulverization process, first, strong pulverization is performed using a roller compactor or a hammer mill. Then, pulverization is performed for 1 to 5 hours using a wet ball mill. At this point, the crystallinity of the product is reduced, so the crystallite size is small. Next, reheat treatment is performed at a temperature equivalent to the temperature during the main firing. The reheat treatment is, for example, a heat treatment for 0.5 to 5 hours. For the reheat treatment, it is preferable to use an electric furnace that has been heated to the target temperature in advance. In addition, after the reheat treatment, it is preferable to quickly cool the powder. In this way, particle growth during heating and cooling of the electric furnace can be suppressed. The cooling after the reheat treatment is preferably performed under conditions in which the temperature of the powder after firing is 100°C or less within 1 hour from the temperature during firing.

[0041] In this way, after carrying out the crushing step including the strong crushing, for example, by carrying out a re-heat treatment at the same temperature as the main firing, the decrease in crystallinity due to crushing can be recovered and particles with a large crystallite size can be obtained. By using a manufacturing method including the strong crushing step and the re-heat treatment step, active material particles with high crystallinity and small average primary particle size can be manufactured.

[0042] Furthermore, by using a flux containing at least S, it is possible to obtain an active material in which the necking ratio N falls within the above-mentioned range.

[0043] The material used in the flux also affects particle growth. When a substance such as sulfate containing S is used as a flux, it has a relatively low melting point and is easily volatile, so the effect of the flux can be easily obtained even when sintered at a low temperature. On the other hand, since it is difficult to form a stable phase similar to the parent phase, even if S flux is present in high concentration, impurity phases are unlikely to form. On the other hand, since the solubility of the solute is low, the effect of promoting grain growth is not that great, and the effect of adding flux on secondary particle size is low. Therefore, S flux can be expected to have an effect such as promoting particle necking.

[0044] When P is used as a raw material for the flux, raw materials such as phosphates have a high melting point. Therefore, in order to obtain sufficient vapor pressure near the surface of the active material particles to function as a flux, sintering at a relatively high temperature is required. Regarding the solubility in the active material to be the solute, the presence of energetically stable phosphates of titanium and niobium makes it easy to dissolve the raw material of the negative electrode active material to be the solute. Therefore, at high temperatures where the P flux is sufficiently melted, it has a high effect of promoting particle growth and has the effect of increasing the primary particle size. On the other hand, when the concentration of P flux is high, these phosphates are easily generated as impurities, so excessive addition leads to a decrease in the purity of the active material.

[0045] For fluxes containing K, compounds with low melting points such as KCl and KNO3 can provide the same effect as S mentioned above. The melting points of these substances tend to be even lower than sulfates, so the flux effect can be expected even at lower temperatures. Furthermore, since there are many stable phases on the K2O-Nb2O5 phase diagram, high solubility can be expected for the active material that is the solute. For this reason, K flux, like P flux, exhibits the function of promoting grain growth. In addition, in the case of K flux, K-containing substances can become impurities, just like P flux.

[0046] The K and P impurities can form grain boundaries between crystallites of the niobium-containing oxide. In addition to the impurity elements, these grain boundaries can contain niobium, just like the parent phase. A part of such grain boundaries becomes a necking portion between primary particles. It is desirable that the concentration of the impurity elements at the grain boundaries is 20% or more higher than the concentration in the parent phase. In other words, the purity of the parent phase is increased by the impurities remaining at the grain boundaries, resulting in good performance as an active material.

[0047] The niobium titanium oxide synthesized by the above method may have lithium ions inserted by charging the battery, or may be synthesized as an oxide containing lithium by using a compound containing lithium such as lithium carbonate as a starting material, as described above.

[0048] Hereinafter, the necking ratio N (relationship (LL cl The method for measuring the relative humidity (H2O2) and the like is described below.

[0049] <Measurement of necking ratio N> Quantitative evaluation of necking between active materials can be performed by analyzing scanning electron microscope (SEM) images of the cross section of an electrode containing the active materials.

[0050] The cross section of the electrode sample is cut out by Ar ion milling and observed by SEM.

[0051] The magnification of the SEM image is preferably about 5000x to balance the number of particles measured and the resolution. The total number of particles to be measured should be 100 or more to improve quantitative accuracy. If it is difficult to observe 100 particles in one SEM image, multiple fields of view should be combined to observe a total of 100 or more particles for analysis. The detection mode should be selected so that the outer periphery of the active material particles can be clearly observed and the active material to be measured can be clearly distinguished from other components based on contrast.

[0052] Analysis software such as ImageJ can be used to binarize the acquired SEM image. First, the SEM image is converted to an 8-bit monochrome image, and then a threshold is set to convert it into a binary image that is displayed only with brightness 0 (black) and 255 (white). It is preferable to use a discriminant analysis method that can set a threshold that maximizes the degree of separation. The obtained binary image is subjected to erode processing with the active material particles assigned to a brightness of 255, and each closed area of ​​the observed brightness of 255 is shrunk by one pixel. This eliminates the connections between adjacent particles and noise, making the particle boundaries clear. Particle analysis is performed on the obtained image to measure the total number of particles n and the total circumference L of the primary particles. Furthermore, the average particle diameter D can be calculated by D=L / nπ, assuming that all particles are perfectly circular.

[0053] Next, dilute processing is performed on the original binarized image, and each closed area of ​​observed brightness 255 is expanded by one pixel. Then, erode processing is performed twice. This closing process fills the tiny gaps between particles that were detected in the original binarized image. After that, particle analysis is performed as before, and the total number of particles and the sum of the perimeters of the primary particles excluding the necking part, L, are calculated. cl Measure the L cl represents the total perimeter of the primary particles excluding the necked portion. This is an analysis method that utilizes the fact that in necked active material particles, the necked portion breaks due to volume changes caused by charging and discharging. The gaps that are different from necking and that form between particles that are simply adjacent to each other from the beginning do not change before and after the dilute treatment. On the other hand, in the case of necked areas, the gaps are filled by the closing treatment, so they are not measured as perimeters in the images after the closing treatment. Therefore, LL cl Value (L to L cl The ratio N of the necked area of ​​the particle is N = (LL cl ) / L.

[0054] Measurements using cross-sectional SEM are made by cutting a part of the necking surface along an arbitrary line, and depending on the area cut, the length of the same necking surface will differ depending on how it is cut. For this reason, in order to quantify information corresponding to the total area of ​​the necking region using analysis of cross-sectional SEM images, analysis is performed on a sufficient number of particles (100 or more).

[0055] Examples of cross-sectional SEM images and processed images are shown in Figs. 3 to 5. Fig. 3 is an example of an SEM image of an electrode cross section. Fig. 4 is an image obtained by binarizing the SEM image of Fig. 3 and then eroding without diluting. Fig. 5 is a processed image obtained by binarizing the SEM image of Fig. 3 and then diluting and eroding twice (closing). The boundaries 16 observed between particles in Fig. 4 are not visible in Fig. 5 after closing. The boundaries 16 that disappear by closing correspond to the necking part of the active material before charging and discharging. The total perimeter L of the primary particles can be obtained by measuring the total length of the perimeter 15 of the active material particles in Fig. 4, including the boundaries 16 corresponding to the necking part. In Fig. 5, the part corresponding to the necking part is excluded from the perimeter 15, so the total perimeter L excluding the necking part can be obtained by measuring the total length of the perimeter 15 in Fig. 5. cl is required.

[0056] <Confirmation of crystal structure and crystallite size of active material> The crystal structure and crystallite size of the active material can be confirmed, for example, by combining powder X-ray diffraction measurement (XRD) and analysis by the Rietveld method.

[0057] The powder X-ray diffraction measurement of the active material can be carried out, for example, as follows.

[0058] First, the active material is crushed as necessary to prepare a sample with an average particle size of less than about 5 μm. The average particle size can be determined by laser diffraction. The obtained sample is filled into a holder portion with a depth of 0.2 mm formed on a glass sample plate. Next, another glass plate is pressed from the outside to flatten the surface of the filled sample. Care should be taken to fill the sample with just the right amount of sample so that cracks, voids, unevenness, etc. do not occur in the filled sample. Also, care should be taken to press the glass plate with sufficient pressure. Next, the glass plate filled with the sample is placed in a powder X-ray diffractometer, and an XRD pattern is obtained using Cu-Kα radiation.

[0059] In addition, when the sample has a high degree of orientation, the peak position may shift or the peak intensity ratio may change depending on how the sample is filled. Such samples with a very high degree of orientation are measured using a capillary. Specifically, the sample is inserted into a capillary, which is then placed on a rotating sample stage for measurement. This measurement method can reduce the degree of orientation. The capillary used is made of Lindemann glass.

[0060] The active material contained in the battery as an electrode material can be measured as follows. First, the active material in the electrode material (e.g., niobium titanium oxide) is placed in a state in which lithium ions are completely removed. For example, when this active material is used in the negative electrode, the battery is placed in a completely discharged state. This allows the crystal state of the active material to be observed. Residual lithium ions may be present even in a discharged state. Due to the influence of residual lithium ions in the electrode, impurity phases such as lithium carbonate and lithium fluoride may be mixed into the powder X-ray diffraction measurement results. The mixing of impurity phases can be prevented, for example, by using an inert gas atmosphere for the measurement or by cleaning the electrode surface. Even if impurity phases are present, it is possible to perform the analysis while ignoring these phases.

[0061] Next, the battery is disassembled in an argon-filled glove box to remove the electrodes. The electrodes are then washed with a suitable solvent, such as ethyl methyl carbonate. The washed electrodes are cut into pieces with an area roughly equal to the area of ​​the holder of the powder X-ray diffraction apparatus to prepare the measurement sample.

[0062] The cut sample (electrode) is directly attached to a glass holder and measured. At this time, the position of the peak derived from the electrode substrate such as a metal foil is measured in advance. In addition, the peaks of other components such as conductive agents and binders are also measured in advance. When the peak of the substrate and the peak of the active material overlap, it is desirable to peel off the layer containing the active material from the substrate (for example, the active material-containing layer described later) and provide it for measurement. This is to separate the overlapping peaks when quantitatively measuring the peak intensity. For example, the active material layer can be peeled off by irradiating the electrode substrate with ultrasonic waves in a solvent. The active material layer is sealed in a capillary and placed on a rotating sample stage for measurement. By this method, the influence of orientation can be reduced and an XRD pattern of the active material can be obtained. The XRD pattern obtained at this time must be applicable to Rietveld analysis. To collect Rietveld data, the step width is set to 1 / 3 to 1 / 5 of the minimum half-width of the diffraction peak, and the measurement time and / or X-ray intensity are appropriately adjusted so that the intensity at the peak position of the most intense reflection is 5,000 to 10,000 counts.

[0063] The obtained XRD pattern is analyzed by the Rietveld method, in which the diffraction pattern is calculated from a pre-estimated crystal structure model. By fitting all of these calculated values ​​with the actual measured values, the parameters related to the crystal structure (lattice constants, atomic coordinates, occupancy, etc.) can be precisely analyzed. This makes it possible to investigate the characteristics of the crystal structure of the synthesized oxide. It is also possible to investigate the occupancy rate of each site of the constituent elements.

[0064] To determine the crystallite diameter (crystallite size), the diffraction line with the strongest diffraction intensity is selected. For example, in the case of monoclinic niobium titanium oxide, the peak of the (110) plane is measured. The crystallite size can be calculated from the half-width of the obtained peak. Here, the crystallite size is calculated using the Scherrer formula shown in Equation 1 below.

[0065]

number

[0066] Here, K=0.9, λ=0.15406 nm, β e : Half-width of diffraction peak, β o : Corrected half-width value (0.07°).

[0067] <How to confirm the composition of active materials> The composition of the active material can be analyzed, for example, by using inductively coupled plasma (ICP) emission spectroscopy. At this time, the abundance ratio (molar ratio) of each element depends on the sensitivity of the analysis device used. Therefore, the measured molar ratio may deviate from the actual molar ratio by the error of the measurement device. However, even if the numerical value deviates within the error range of the analysis device, the performance of the active material according to the embodiment can be fully exhibited.

[0068] Specifically, the composition of the active material incorporated in the battery is measured by ICP emission spectroscopy according to the following procedure.

[0069] First, the electrode containing the active material to be measured is removed from the secondary battery and washed according to the procedure described in the section on powder X-ray diffraction. The part containing the electrode active material, such as the active material-containing layer, is peeled off from the washed electrode. For example, the part containing the electrode active material can be peeled off by irradiating it with ultrasonic waves. As a specific example, the electrode can be placed in ethyl methyl carbonate in a glass beaker and vibrated in an ultrasonic cleaner to peel off the active material-containing layer containing the electrode active material from the electrode current collector.

[0070] Next, the peeled off part is heated in air for a short time (for example, at 500°C for about an hour) to burn off unnecessary components such as the binder component and conductive agent (for example, carbon material) described below. This residue can be dissolved in acid to create a liquid sample containing the active material. The acid that can be used in this case is hydrochloric acid, nitric acid, sulfuric acid, hydrogen fluoride, etc. This liquid sample can be subjected to ICP analysis to determine the composition of the active material.

[0071] <How to check for impurity elements> The concentrations of impurity elements in the matrix phase of the niobium-containing oxide and in the grain boundaries between crystallites can be measured as follows.

[0072] The necking sites at the particle boundaries of the active material are observed using a transmission electron microscope (TEM). The composition of the grain boundaries is quantified using energy dispersive X-ray spectroscopy (EDX), and can be compared with the composition of the parent phase. This allows the amount of impurity elements unevenly distributed at the grain boundaries to be quantified.

[0073] Second Embodiment According to a second embodiment, an electrode is provided.

[0074] The electrode according to the second embodiment includes the active material according to the first embodiment. This electrode can be a battery electrode that includes the active material according to the first embodiment as a battery active material. The electrode as a battery electrode can be, for example, a negative electrode that includes the active material according to the first embodiment as a negative electrode active material.

[0075] Such an electrode may include a current collector and an active material-containing layer. The active material-containing layer may be formed on one or both sides of the current collector. The active material-containing layer may include an active material and, optionally, a conductive agent and a binder.

[0076] The conductive agent is blended to improve the current collecting performance and to reduce the contact resistance between the active material and the current collector. Examples of the conductive agent include carbonaceous materials such as vapor grown carbon fiber (VGCF), carbon black such as acetylene black, graphite, carbon nanotubes, and carbon nanofibers. One of these may be used as the conductive agent, or two or more may be used in combination as the conductive agent. Alternatively, instead of using a conductive agent, a carbon coating or an electronically conductive inorganic material coating may be applied to the surface of the active material particles.

[0077] The binder is blended to fill the gaps between the dispersed active materials and to bind the active materials and the current collector. Examples of the binder include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), fluorine-based rubber, styrene butadiene rubber, polyacrylic acid compounds, imide compounds, carboxymethyl cellulose (CMC), and salts of CMC. One of these may be used as the binder, or two or more may be used in combination as the binder.

[0078] The mixing ratio of the active material, conductive agent and binder in the active material-containing layer can be appropriately changed depending on the application of the electrode. For example, when the electrode is used as a negative electrode of a secondary battery, it is preferable to mix the active material (negative electrode active material), conductive agent and binder at a ratio of 68% by mass or more and 96% by mass or less, 2% by mass or more and 30% by mass or less, and 2% by mass or more and 30% by mass or less, respectively. By making the amount of the conductive agent 2% by mass or more, the current collection performance of the active material-containing layer can be improved. In addition, by making the amount of the binder 2% by mass or more, the binding property between the active material-containing layer and the current collector becomes sufficient, and excellent cycle performance can be expected. On the other hand, it is preferable to make the conductive agent and the binder 30% by mass or less, respectively, in order to increase the capacity.

[0079] The current collector is made of a material that is electrochemically stable at the potential at which lithium (Li) is inserted and removed from the active material. For example, when the active material is used as a negative electrode active material, the current collector is preferably made of copper, nickel, stainless steel, or aluminum, or an aluminum alloy containing one or more elements selected from Mg, Ti, Zn, Mn, Fe, Cu, and Si. The thickness of the current collector is preferably 5 μm or more and 20 μm or less. A current collector having such a thickness can balance the strength and weight of the electrode.

[0080] The current collector may also include a portion on the surface of which the negative electrode active material-containing layer is not formed, and this portion can function as a negative electrode current collecting tab.

[0081] The electrode can be produced, for example, by the following method. First, an active material, a conductive agent, and a binder are suspended in a solvent to prepare a slurry. This slurry is applied to one or both sides of a current collector. Next, the applied slurry is dried to obtain a laminate of an active material-containing layer and a current collector. After that, the laminate is pressed. In this manner, an electrode is produced.

[0082] Alternatively, the electrode may be prepared by the following method: first, the active material, the conductive agent, and the binder are mixed to obtain a mixture, then the mixture is formed into pellets, and then the pellets are placed on a current collector to obtain an electrode.

[0083] The electrode according to the second embodiment contains the active material according to the first embodiment, and therefore, this electrode can provide a secondary battery with high output performance and excellent life performance.

[0084] (Third embodiment) According to a third embodiment, a secondary battery is provided that includes a positive electrode, a negative electrode including a negative electrode active material, and an electrolyte. The negative electrode active material includes secondary particles including a plurality of primary particles including a niobium-containing oxide. The secondary particles include a first adjacent portion where the primary particles are adjacent to each other, and a second adjacent portion where the primary particles are in contact with each other via an interface. The total perimeter L of the primary particles and the sum of the perimeters of the primary particles excluding the second adjacent portion L cl That is, 0.1≦(LL cl ) / L≦0.6.

[0085] This secondary battery may be a battery including the electrode according to the second embodiment as the negative electrode. In other words, the secondary battery according to the third embodiment may be a battery including, as the negative electrode, an electrode including the active material according to the first embodiment as a battery active material. However, as explained in the first embodiment, the necking portion of the active material breaks due to a volume change caused by charging and discharging. That is, the second adjacent portion corresponds to the portion where the necking breaks. The first adjacent portion corresponds to the portion where the primary particles were adjacent to each other before the necking breaks. The above relational formula (LL cl ) / L represents the proportion of the second adjacent portion, which corresponds to the necking ratio N. (LL cl The method for measuring the concentration of 100 mM KOH / L was as described above.

[0086] The secondary battery may further include a separator disposed between the positive electrode and the negative electrode. The negative electrode, the positive electrode, and the separator may constitute an electrode group. The electrolyte may be held in the electrode group.

[0087] Moreover, such a secondary battery can further include an exterior member that houses the electrode group and the electrolyte.

[0088] Furthermore, such a secondary battery may further include a negative electrode terminal electrically connected to the negative electrode and a positive electrode terminal electrically connected to the positive electrode.

[0089] Such a secondary battery may be, for example, a lithium secondary battery. The secondary battery also includes a non-aqueous electrolyte secondary battery that contains a non-aqueous electrolyte.

[0090] The negative electrode, the positive electrode, the electrolyte, the separator, the exterior member, the negative electrode terminal, and the positive electrode terminal will be described in detail below.

[0091] 1) Negative electrode The negative electrode may include a negative electrode current collector and a negative electrode active material-containing layer. The negative electrode current collector and the negative electrode active material-containing layer may be the current collector and the active material-containing layer that can be included in the electrode according to the second embodiment, respectively. The negative electrode active material-containing layer includes the active material according to the first embodiment as a negative electrode active material.

[0092] Among the details of the negative electrode, those parts that overlap with the details explained in the second embodiment will be omitted.

[0093] The density of the negative electrode active material-containing layer (excluding the current collector) is 1.8 g / cm 3 More than 2.8g / cm 3 A negative electrode having a density of the negative electrode active material-containing layer within this range is excellent in energy density and electrolyte retention. The density of the negative electrode active material-containing layer is preferably 2.1 g / cm or less. 3 More than 2.6g / cm 3 It is more preferable that:

[0094] The negative electrode can be produced, for example, by the same method as that for the electrode according to the second embodiment.

[0095] 2) Positive electrode The positive electrode may include a positive electrode current collector and a positive electrode active material-containing layer. The positive electrode active material-containing layer may be formed on one or both sides of the positive electrode current collector. The positive electrode active material-containing layer may include a positive electrode active material, and optionally a conductive agent and a binder.

[0096] As the positive electrode active material, for example, an oxide or a sulfide can be used. The positive electrode may contain one type of compound alone as the positive electrode active material, or may contain two or more types of compounds in combination. Examples of oxides and sulfides include compounds that can insert and remove Li or Li ions.

[0097] Examples of such compounds include, for example, manganese dioxide (MnO2), iron oxide, copper oxide, nickel oxide, lithium manganese composite oxide (e.g., Li x Mn2O4 or Li x MnO2; 0 < x ≦ 1), lithium nickel composite oxide (e.g., Li x NiO2; 0 < x ≦ 1), lithium cobalt composite oxide (e.g., Li x CoO2; 0 < x ≦ 1), lithium nickel cobalt composite oxide (e.g., Li x Ni 1-y Co y O2; 0 < x ≦ 1, 0 < y < 1), lithium manganese cobalt composite oxide (e.g., Li x Mn y Co 1-y O2; 0 < x ≦ 1, 0 < y < 1), lithium manganese nickel composite oxide having a spinel structure (e.g., Li x Mn 2-y Ni y O4; 0 < x ≦ 1, 0 < y < 2), lithium phosphate having an olivine structure (e.g., Li x FePO4; 0 < x ≦ 1, Li x Fe 1-y Mn y PO4; 0 < x ≦ 1, 0 < y ≦ 1, Li x CoPO4; 0 < x ≦ 1), iron sulfate (Fe2(SO4)3), vanadium oxide (e.g., V2O5), and lithium nickel cobalt manganese composite oxide (Li x Ni 1-y-z Co y Mn z O2; 0 < x ≦ 1, 0 < y < 1, 0 < z < 1, y + z < 1) are included.

[0098] Among the above, examples of more preferable compounds as the positive electrode active material include lithium manganese composite oxide having a spinel structure (e.g., Li x Mn2O4; 0 < x ≦ 1), lithium nickel composite oxide (e.g., Li x NiO2; 0 < x ≦ 1), lithium cobalt composite oxide (e.g., Li xCoO2; 0 < x ≦ 1), lithium nickel cobalt composite oxide (e.g., Li x Ni 1-y Co y O2; 0 < x ≦ 1, 0 < y < 1), lithium manganese nickel composite oxide having a spinel structure (e.g., Li x Mn 2-y Ni y O4; 0 < x ≦ 1, 0 < y < 2), lithium manganese cobalt composite oxide (e.g., Li x Mn y Co 1-y O2; 0 < x ≦ 1, 0 < y < 1), lithium iron phosphate (e.g., Li x FePO4; 0 < x ≦ 1), and lithium nickel cobalt manganese composite oxide (Li x Ni 1-y-z Co y Mn z O2; 0 < x ≦ 1, 0 < y < 1, 0 < z < 1, y + z < 1) are included. When these compounds are used as the positive electrode active material, the positive electrode potential can be increased.

[0099] When using a room temperature molten salt as the electrolyte of the battery, it is preferable to use a positive electrode active material containing lithium iron phosphate, Li x VPO4F (0 ≦ x ≦ 1), lithium manganese composite oxide, lithium nickel composite oxide, lithium nickel cobalt composite oxide, or a mixture thereof. Since these compounds have low reactivity with the room temperature molten salt, the cycle life can be improved. Details of the room temperature molten salt will be described later.

[0100] The primary particle size of the positive electrode active material is preferably 100 nm or more and 1 μm or less. A positive electrode active material with a primary particle size of 100 nm or more is easy to handle in industrial production. A positive electrode active material with a primary particle size of 1 μm or less can allow the solid-state diffusion of lithium ions to proceed smoothly.

[0101] The specific surface area of the positive electrode active material is preferably 0.1 m 2 / g or more and 10 m 2 / g or less. A positive electrode active material with a specific surface area of 0.1 m 2A positive electrode active material having a specific surface area of ​​10m / g or more can secure sufficient sites for absorbing and releasing Li ions. 2 A positive electrode active material having a specific surface area of ​​100 / g or less is easy to handle in industrial production and can ensure good charge-discharge cycle performance.

[0102] The binder is blended to fill the gaps between the dispersed positive electrode active material and to bind the positive electrode active material and the positive electrode current collector. Examples of the binder include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), fluorine-based rubber, polyacrylic acid compounds, imide compounds, carboxymethyl cellulose (CMC), and salts of CMC. One of these may be used as the binder, or two or more may be used in combination as the binder.

[0103] The conductive agent is blended to improve current collection performance and reduce contact resistance between the positive electrode active material and the positive electrode current collector. Examples of the conductive agent include vapor grown carbon fiber (VGCF), carbon black such as acetylene black, and carbonaceous materials such as graphite. One of these may be used as the conductive agent, or two or more may be combined and used as the conductive agent. The conductive agent may also be omitted.

[0104] In the positive electrode active material-containing layer, the positive electrode active material and the binder are preferably mixed in proportions of 80% by mass to 98% by mass and 2% by mass to 20% by mass, respectively.

[0105] By making the amount of binder 2% by mass or more, sufficient electrode strength can be obtained. In addition, the binder can function as an insulator. Therefore, by making the amount of binder 20% by mass or less, the amount of insulator contained in the electrode is reduced, and the internal resistance can be reduced.

[0106] When a conductive agent is added, the positive electrode active material, the binder, and the conductive agent are preferably mixed in proportions of 77% by mass or more and 95% by mass or less, 2% by mass or more and 20% by mass or less, and 3% by mass or more and 15% by mass or less, respectively.

[0107] By setting the amount of the conductive agent to 3% by mass or more, the above-mentioned effects can be achieved. Also, by setting the amount of the conductive agent to 15% by mass or less, the ratio of the conductive agent in contact with the electrolyte can be reduced. If this ratio is low, decomposition of the electrolyte during high-temperature storage can be reduced.

[0108] The positive electrode current collector is preferably an aluminum foil or an aluminum alloy foil containing one or more elements selected from Mg, Ti, Zn, Ni, Cr, Mn, Fe, Cu, and Si.

[0109] The thickness of the aluminum foil or aluminum alloy foil is preferably 5 μm or more and 20 μm or less, more preferably 15 μm or less. The purity of the aluminum foil is preferably 99 mass% or more. The content of transition metals such as iron, copper, nickel, and chromium contained in the aluminum foil or aluminum alloy foil is preferably 1 mass% or less.

[0110] The positive electrode current collector may also include a portion on the surface of which the positive electrode active material-containing layer is not formed, and this portion can function as a positive electrode current collecting tab.

[0111] The positive electrode can be produced, for example, by using a positive electrode active material in the same manner as in the electrode according to the second embodiment.

[0112] 3) Electrolyte The electrolyte may be, for example, a liquid nonaqueous electrolyte or a gel nonaqueous electrolyte. The liquid nonaqueous electrolyte is prepared by dissolving an electrolyte salt as a solute in an organic solvent. The concentration of the electrolyte salt is preferably 0.5 mol / L or more and 2.5 mol / L or less.

[0113] Examples of the electrolyte salt include lithium salts such as lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium trifluoromethanesulfonate (LiCF3SO3), and lithium bistrifluoromethylsulfonylimide (LiN(CF3SO2)2), and mixtures thereof. The electrolyte salt is preferably one that is difficult to oxidize even at high potentials, and LiPF6 is most preferred.

[0114] Examples of organic solvents include cyclic carbonates such as propylene carbonate (PC), ethylene carbonate (EC), and vinylene carbonate (VC); chain carbonates such as diethyl carbonate (DEC), dimethyl carbonate (DMC), and methyl ethyl carbonate (MEC); cyclic ethers such as tetrahydrofuran (THF), 2-methyl tetrahydrofuran (2MeTHF), and dioxolane (DOX); chain ethers such as dimethoxyethane (DME) and diethoxyethane (DEE); γ-butyrolactone (GBL), acetonitrile (AN), and sulfolane (SL). These organic solvents can be used alone or as a mixed solvent.

[0115] The gelled non-aqueous electrolyte is prepared by combining a liquid non-aqueous electrolyte with a polymeric material, such as polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyethylene oxide (PEO), or a mixture thereof.

[0116] Alternatively, as the nonaqueous electrolyte, in addition to liquid nonaqueous electrolytes and gel nonaqueous electrolytes, room temperature molten salts containing lithium ions (ionic melts), polymer solid electrolytes, inorganic solid electrolytes, and the like may be used.

[0117] Room temperature molten salts (ionic melts) refer to organic salts consisting of a combination of organic cations and anions that can exist as a liquid at room temperature (15°C or higher and 25°C or lower). Room temperature molten salts include room temperature molten salts that exist as a liquid by themselves, room temperature molten salts that become liquid when mixed with an electrolyte salt, room temperature molten salts that become liquid when dissolved in an organic solvent, and mixtures of these. In general, the melting point of room temperature molten salts used in secondary batteries is 25°C or lower. In addition, organic cations generally have a quaternary ammonium skeleton.

[0118] The polymer solid electrolyte is prepared by dissolving an electrolyte salt in a polymer material and solidifying it.

[0119] The inorganic solid electrolyte is a solid substance that has Li-ion conductivity. Here, Li-ion conductivity is defined as a Li-ion conductivity of 1×10 -6 It means that the inorganic solid electrolyte has a lithium ion conductivity of 1.0 S / cm or more. Examples of the inorganic solid electrolyte include oxide-based solid electrolytes and sulfide-based solid electrolytes. Specific examples of the inorganic solid electrolyte are as follows.

[0120] The oxide-based solid electrolyte has a NASICON (Sodium (Na) Super Ionic Conductor) type structure and is represented by the general formula Li 1+x Mα 2(It is preferable to use a lithium phosphate solid electrolyte represented by (PO4)3. In the above general formula, Mα is, for example, one or more selected from the group consisting of titanium (Ti), germanium (Ge), strontium (Sr), zirconium (Zr), tin (Sn), aluminum (Al), and calcium (Ca). The subscript x is within the range of 0 ≦ x ≦ 2.

[0121] Specific examples of the lithium phosphate solid electrolyte having a NASICON-type structure include Li 1+x Al x Ti 2-x (PO4)3, and the LATP compound where 0.1 ≦ x ≦ 0.5; Li 1+x Al y Mβ 2-y (PO4)3, where Mβ is one or more selected from the group consisting of Ti, Ge, Sr, Zr, Sn, and Ca, and 0 ≦ x ≦ 1 and 0 ≦ y ≦ 1; Li 1+x Al x Ge 2-x (PO4)3, and the compound where 0 ≦ x ≦ 2; and, Li 1+x Al x Zr 2-x (PO4)3, and the compound where 0 ≦ x ≦ 2; Li 1+x+y Al x Mγ 2-x Si y P 3-y O 12 represented by, where Mγ is one or more selected from the group consisting of Ti and Ge, and 0 < x ≦ 2, 0 ≦ y < 3; Li 1+2x Zr 1-x Ca x (PO4)3, and the compound where 0 ≦ x < 1 can be mentioned.

[0122] In addition, as the oxide-based solid electrolyte, in addition to the above lithium phosphate solid electrolyte, there is also an amorphous LIPON compound represented by Li x PO y N z where 2.6 ≦ x ≦ 3.5, 1.9 ≦ y ≦ 3.8, and 0.1 ≦ z ≦ 1.3 (for example, Li 2.9P O 3.3 N 0.46); Garnet-type structure La 5+x A x La 3-x MδO 12 A is 1 or more selected from the group consisting of Ca, Sr, and Ba, Mδ is 1 or more selected from the group consisting of Nb and Ta, and 0≦x≦0.5; Li3Mδ 2-x L2O 12 wherein Mδ is at least one selected from the group consisting of Nb and Ta, and L may contain Zr, and 0≦x≦0.5; Li 7-3x Al x La3Zr3O 12 and 0≦x≦0.5; Li 5+x La3Mδ 2-x Zr x O 12 where Mδ is at least one selected from the group consisting of Nb and Ta, and 0≦x≦2. LLZ compounds (e.g., Li7La3Zr2O 12 ); and La 2 / 3-x Li x Examples of such compounds include those represented by TiO3, where x is 0.3≦x≦0.7.

[0123] One or more of the above compounds can be used as the solid electrolyte. Two or more of the above solid electrolytes can also be used.

[0124] 4) Separator The separator is formed, for example, from a porous film containing polyethylene (PE), polypropylene (PP), cellulose, or polyvinylidene fluoride (PVdF), or a synthetic resin nonwoven fabric. From the viewpoint of safety, it is preferable to use a porous film formed from polyethylene or polypropylene. This is because these porous films melt at a certain temperature and are capable of cutting off electric current.

[0125] 5) Exterior materials As the exterior member, for example, a container made of a laminate film or a metal container can be used.

[0126] The thickness of the laminate film is, for example, 0.5 mm or less, preferably 0.2 mm or less.

[0127] The laminate film is a multi-layer film including a plurality of resin layers and a metal layer interposed between the resin layers. The resin layers include polymeric materials such as polypropylene (PP), polyethylene (PE), nylon, and polyethylene terephthalate (PET). The metal layer is preferably made of aluminum foil or aluminum alloy foil for weight reduction. The laminate film can be molded into the shape of the exterior member by sealing it by heat fusion.

[0128] The thickness of the wall of the metal container is, for example, 1 mm or less, more preferably 0.5 mm or less, and even more preferably 0.2 mm or less.

[0129] The metal container is made of, for example, aluminum or an aluminum alloy. The aluminum alloy preferably contains elements such as magnesium, zinc, and silicon. When the aluminum alloy contains transition metals such as iron, copper, nickel, and chromium, the content of the transition metals is preferably 100 ppm by mass or less.

[0130] The shape of the exterior member is not particularly limited. The shape of the exterior member may be, for example, flat (thin), rectangular, cylindrical, coin, or button. The exterior member can be appropriately selected depending on the battery dimensions and the application of the battery.

[0131] 6) Negative terminal The negative electrode terminal can be made of a material that is electrochemically stable at the Li absorption / release potential of the negative electrode active material and has electrical conductivity. Specifically, the material of the negative electrode terminal can be copper, nickel, stainless steel, aluminum, or an aluminum alloy containing at least one element selected from the group consisting of Mg, Ti, Zn, Mn, Fe, Cu, and Si. The material of the negative electrode terminal is preferably aluminum or an aluminum alloy. The negative electrode terminal is preferably made of the same material as the negative electrode current collector in order to reduce the contact resistance with the negative electrode current collector.

[0132] 7) Positive terminal The positive electrode terminal has a potential range of 3V to 4.5V with respect to the redox potential of lithium (vs. Li / Li + ) and can be formed from a material that is electrically stable and conductive. Examples of the material for the positive electrode terminal include aluminum and an aluminum alloy containing at least one element selected from the group consisting of Mg, Ti, Zn, Mn, Fe, Cu, and Si. The positive electrode terminal is preferably formed from the same material as the positive electrode current collector in order to reduce the contact resistance with the positive electrode current collector.

[0133] Next, the secondary battery according to the embodiment will be described more specifically with reference to the drawings.

[0134] Fig. 6 is a cross-sectional view showing an example of a secondary battery, and Fig. 7 is an enlarged cross-sectional view of part A of the secondary battery shown in Fig. 6.

[0135] The secondary battery 100 shown in Figures 6 and 7 includes a bag-shaped exterior member 2 shown in Figure 6, an electrode group 1 shown in Figures 6 and 7, and an electrolyte (not shown). The electrode group 1 and the electrolyte are stored in the bag-shaped exterior member 2. The electrolyte (not shown) is held in the electrode group 1.

[0136] The bag-shaped exterior member 2 is made of a laminate film including two resin layers and a metal layer interposed between them.

[0137] As shown in Fig. 6, the electrode group 1 is a flat wound-type electrode group. As shown in Fig. 7, the flat wound-type electrode group 1 includes a negative electrode 3, a separator 4, and a positive electrode 5. The separator 4 is interposed between the negative electrode 3 and the positive electrode 5.

[0138] The negative electrode 3 includes a negative electrode current collector 3a and a negative electrode active material-containing layer 3b. In the negative electrode 3, in a portion located at the outermost shell of the wound-type electrode group 1, the negative electrode active material-containing layer 3b is formed only on the inner surface side of the negative electrode current collector 3a as shown in Fig. 7. In the other portions of the negative electrode 3, the negative electrode active material-containing layer 3b is formed on both sides of the negative electrode current collector 3a.

[0139] The positive electrode 5 includes a positive electrode current collector 5a and a positive electrode active material-containing layer 5b formed on both sides of the positive electrode current collector 5a.

[0140] As shown in FIG. 6, the negative electrode terminal 6 and the positive electrode terminal 7 are located near the outer peripheral end of the wound electrode group 1. The negative electrode terminal 6 is connected to a portion located at the outermost shell of the negative electrode current collector 3a. The positive electrode terminal 7 is connected to a portion located at the outermost shell of the positive electrode current collector 5a. The negative electrode terminal 6 and the positive electrode terminal 7 extend to the outside from an opening of the bag-shaped exterior member 2. A thermoplastic resin layer is provided on the inner surface of the bag-shaped exterior member 2, and the opening is closed by heat sealing.

[0141] The secondary battery according to the embodiment is not limited to the secondary battery having the configuration shown in FIGS. 6 and 7, but may be a battery having the configuration shown in FIGS. 8 and 9, for example.

[0142] Fig. 3 is a partially cutaway perspective view showing a schematic diagram of another example of the secondary battery. Fig. 9 is an enlarged cross-sectional view of part B of the secondary battery shown in Fig. 8.

[0143] The secondary battery 100 shown in Figures 8 and 9 includes an electrode group 1 shown in Figures 8 and 9, an exterior member 2 shown in Figure 8, and an electrolyte (not shown). The electrode group 1 and the electrolyte are housed in the exterior member 2. The electrolyte is held in the electrode group 1.

[0144] The exterior member 2 is made of a laminate film including two resin layers and a metal layer interposed between them.

[0145] The electrode group 1 is a laminated type electrode group, as shown in Fig. 9. The laminated type electrode group 1 has a structure in which negative electrodes 3 and positive electrodes 5 are alternately laminated with separators 4 interposed therebetween.

[0146] The electrode group 1 includes a plurality of negative electrodes 3. Each of the plurality of negative electrodes 3 includes a negative electrode current collector 3a and a negative electrode active material-containing layer 3b supported on both sides of the negative electrode current collector 3a. The electrode group 1 also includes a plurality of positive electrodes 5. Each of the plurality of positive electrodes 5 includes a positive electrode current collector 5a and a positive electrode active material-containing layer 5b supported on both sides of the positive electrode current collector 5a.

[0147] The negative electrode current collector 3a of each negative electrode 3 includes a portion on one side where the negative electrode active material-containing layer 3b is not supported on any surface. This portion serves as a negative electrode current collector tab 3c. As shown in FIG. 9, the negative electrode current collector tab 3c does not overlap with the positive electrode 5. The negative electrode current collector tabs 3c are electrically connected to a belt-shaped negative electrode terminal 6. The tip of the belt-shaped negative electrode terminal 6 is pulled out to the outside of the exterior member 2.

[0148] Although not shown, the positive electrode current collector 5a of each positive electrode 5 includes a portion on one side where the positive electrode active material-containing layer 5b is not supported on any surface. This portion serves as a positive electrode current collector tab. The positive electrode current collector tab does not overlap with the negative electrode 3, similar to the negative electrode current collector tab 3c. The positive electrode current collector tab is located on the opposite side of the electrode group 1 to the negative electrode current collector tab 3c. The positive electrode current collector tab is electrically connected to a strip-shaped positive electrode terminal 7. The tip of the strip-shaped positive electrode terminal 7 is located on the opposite side of the negative electrode terminal 6 and is drawn out to the outside of the exterior member 2.

[0149] The secondary battery according to the third embodiment contains the active material according to the first embodiment, and therefore has high output performance and excellent life performance.

[0150] (Fourth embodiment) According to a fourth embodiment, there is provided a battery pack including a plurality of secondary batteries according to the third embodiment.

[0151] In such a battery pack, the individual cells may be electrically connected in series or parallel, or may be arranged in a combination of series and parallel connections.

[0152] Next, an example of a battery pack according to an embodiment will be described with reference to the drawings.

[0153] Fig. 10 is a perspective view showing an example of a battery pack. The battery pack 200 shown in Fig. 10 includes five cells 100a to 100e, four bus bars 21, a positive electrode lead 22, and a negative electrode lead 23. Each of the five cells 100a to 100e is a secondary battery according to the third embodiment.

[0154] The bus bar 21 connects, for example, the negative electrode terminal 6 of one cell 100a and the positive electrode terminal 7 of the adjacent cell 100b. In this way, the five cells 100 are connected in series by the four bus bars 21. That is, the battery pack 200 in FIG. 10 is a five-series battery pack. Although no example is shown, in a battery pack including a plurality of cells electrically connected in parallel, for example, the plurality of negative electrode terminals are connected to each other by a bus bar and the plurality of positive electrode terminals are connected to each other by a bus bar, so that the plurality of cells are electrically connected to each other.

[0155] The positive electrode terminal 7 of at least one of the five cells 100a to 100e is electrically connected to a positive electrode lead 22 for external connection. Also, the negative electrode terminal 6 of at least one of the five cells 100a to 100e is electrically connected to a negative electrode lead 23 for external connection.

[0156] The battery pack according to the fourth embodiment includes the secondary battery according to the third embodiment, and therefore has high output performance and excellent life performance.

[0157] Fifth embodiment According to a fifth embodiment, there is provided a battery pack. The battery pack includes the battery assembly according to the fourth embodiment. The battery pack may include a single secondary battery according to the third embodiment, instead of the battery assembly according to the fourth embodiment.

[0158] Such a battery pack may further include a protection circuit. The protection circuit has a function of controlling charging and discharging of the secondary battery. Alternatively, a circuit included in a device (e.g., electronic device, automobile, etc.) that uses the battery pack as a power source may be used as the protection circuit for the battery pack.

[0159] The battery pack may further include an external terminal for current flow. The external terminal for current flow is for outputting current from the secondary battery to the outside and / or inputting current from the outside to the secondary battery. In other words, when the battery pack is used as a power source, current is supplied to the outside through the external terminal for current flow. When the battery pack is charged, a charging current (including regenerative energy from the power of an automobile or the like) is supplied to the battery pack through the external terminal for current flow.

[0160] Next, an example of a battery pack according to an embodiment will be described with reference to the drawings.

[0161] Fig. 11 is an exploded perspective view showing an example of a battery pack, and Fig. 12 is a block diagram showing an example of an electric circuit of the battery pack shown in Fig. 11.

[0162] The battery pack 300 shown in Figs. 11 and 12 includes a container 31, a lid 32, a protective sheet 33, a battery pack 200, a printed wiring board 34, wiring 35, and an insulating plate (not shown).

[0163] 11 is a bottomed, square container having a rectangular bottom. The container 31 is configured to be able to accommodate a protective sheet 33, a battery pack 200, a printed wiring board 34, and wiring 35. The lid 32 has a rectangular shape. The lid 32 covers the container 31 to accommodate the battery pack 200 and the like. Although not shown, the container 31 and the lid 32 are provided with openings or connection terminals for connection to an external device or the like.

[0164] The battery pack 200 includes a plurality of cells 100, a positive electrode lead 22, a negative electrode lead 23, and an adhesive tape 24.

[0165] At least one of the plurality of unit cells 100 is a secondary battery according to the third embodiment. Each of the plurality of unit cells 100 is electrically connected in series as shown in FIG. 12. The plurality of unit cells 100 may be electrically connected in parallel, or may be connected in a combination of series and parallel connections. When the plurality of unit cells 100 are connected in parallel, the battery capacity is increased compared to when they are connected in series.

[0166] The adhesive tape 24 fastens the plurality of unit cells 100. The plurality of unit cells 100 may be fixed using heat shrink tape instead of the adhesive tape 24. In this case, the protective sheets 33 are disposed on both side surfaces of the battery pack 200, the heat shrink tape is wrapped around the battery pack 200, and the heat shrink tape is then thermally shrunk to bind the plurality of unit cells 100 together.

[0167] One end of the positive electrode lead 22 is connected to the battery pack 200. One end of the positive electrode lead 22 is electrically connected to the positive electrode of one or more cells 100. One end of the negative electrode lead 23 is connected to the battery pack 200. One end of the negative electrode lead 23 is electrically connected to the negative electrode of one or more cells 100.

[0168] The printed wiring board 34 is disposed along one of the short side surfaces of the inner surface of the container 31. The printed wiring board 34 includes a positive connector 342, a negative connector 343, a thermistor 345, a protection circuit 346, wiring 342a and 343a, an external terminal 350 for supplying electricity, a positive wiring (positive wiring) 348a, and a negative wiring (negative wiring) 348b. One main surface of the printed wiring board 34 faces one side of the battery pack 200. An insulating plate (not shown) is interposed between the printed wiring board 34 and the battery pack 200.

[0169] The other end 22a of the positive electrode lead 22 is electrically connected to the positive electrode connector 342. The other end 23a of the negative electrode lead 23 is electrically connected to the negative electrode connector 343.

[0170] The thermistor 345 is fixed to one main surface of the printed wiring board 34. The thermistor 345 detects the temperature of each of the cells 100, and transmits a detection signal to the protection circuit 346.

[0171] The external terminal 350 for current supply is fixed to the other main surface of the printed wiring board 34. The external terminal 350 for current supply is electrically connected to a device present outside the battery pack 300. The external terminal 350 for current supply includes a positive terminal 352 and a negative terminal 353.

[0172] The protection circuit 346 is fixed to the other main surface of the printed wiring board 34. The protection circuit 346 is connected to the positive terminal 352 via a positive wiring 348a. The protection circuit 346 is connected to the negative terminal 353 via a negative wiring 348b. The protection circuit 346 is also electrically connected to the positive electrode connector 342 via a wiring 342a. The protection circuit 346 is electrically connected to the negative electrode connector 343 via a wiring 343a. Furthermore, the protection circuit 346 is electrically connected to each of the plurality of single cells 100 via the wiring 35.

[0173] The protective sheet 33 is disposed on both inner surfaces in the long side direction of the container 31 and on the inner surface in the short side direction that faces the printed wiring board 34 via the battery pack 200. The protective sheet 33 is made of, for example, resin or rubber.

[0174] The protection circuit 346 controls charging and discharging of the multiple cells 100. In addition, the protection circuit 346 cuts off electrical connection between the protection circuit 346 and external terminals 350 (positive terminal 352, negative terminal 353) for supplying electricity to an external device, based on a detection signal transmitted from the thermistor 345, or a detection signal transmitted from each of the cells 100 or the battery pack 200.

[0175] An example of the detection signal transmitted from the thermistor 345 is a signal that detects that the temperature of the cell 100 is equal to or higher than a predetermined temperature. An example of the detection signal transmitted from each cell 100 or the battery pack 200 is a signal that detects overcharging, overdischarging, and overcurrent of the cell 100. When detecting overcharging or the like for each cell 100, the battery voltage may be detected, or the positive electrode potential or the negative electrode potential may be detected. In the latter case, a lithium electrode used as a reference electrode is inserted into each cell 100.

[0176] The protection circuit 346 may be a circuit included in a device (such as an electronic device or an automobile) that uses the battery pack 300 as a power source.

[0177] As described above, the battery pack 300 includes the external terminal 350 for current supply. Therefore, the battery pack 300 can output a current from the assembled battery 200 to an external device and input a current from the external device to the assembled battery 200 via the external terminal 350 for current supply. In other words, when the battery pack 300 is used as a power source, the current from the assembled battery 200 is supplied to the external device through the external terminal 350 for current supply. When the battery pack 300 is charged, a charging current from the external device is supplied to the battery pack 300 through the external terminal 350 for current supply. When the battery pack 300 is used as an in-vehicle battery, regenerative energy of the vehicle's power can be used as the charging current from the external device.

[0178] The battery pack 300 may include a plurality of assembled batteries 200. In this case, the assembled batteries 200 may be connected in series, in parallel, or in a combination of series and parallel connections. The printed wiring board 34 and the wiring 35 may be omitted. In this case, the positive electrode lead 22 and the negative electrode lead 23 may be used as a positive terminal 352 and a negative terminal 353, respectively, of the external terminal 350 for current supply.

[0179] Such a battery pack is used in applications that require excellent cycle performance, for example, when a large current is drawn. Specifically, the battery pack is used, for example, as a power source for electronic devices, a stationary battery, or an on-board battery for various vehicles. An example of the electronic device is a digital camera. The battery pack is particularly suitable for use as an on-board battery.

[0180] The battery pack according to the fifth embodiment includes the secondary battery according to the third embodiment or the battery pack according to the fourth embodiment, and therefore has high output performance and excellent life performance.

[0181] Sixth embodiment According to a sixth embodiment, a vehicle is provided. The vehicle is equipped with the battery pack according to the fifth embodiment.

[0182] In such a vehicle, the battery pack, for example, recovers regenerative energy of the vehicle's motive power. The vehicle may include a mechanism (regenerator) that converts the kinetic energy of the vehicle into regenerative energy.

[0183] Examples of vehicles include, for example, two to four wheel hybrid electric vehicles, two to four wheel electric vehicles, power assisted bicycles, and rail vehicles.

[0184] The mounting position of the battery pack in the vehicle is not particularly limited. For example, when the battery pack is mounted in an automobile, the battery pack can be mounted in the engine compartment, the rear of the vehicle body, or under the seat of the vehicle.

[0185] The vehicle may be equipped with a plurality of battery packs. In this case, the batteries included in each battery pack may be electrically connected in series, electrically connected in parallel, or electrically connected in a combination of series and parallel connections. For example, when each battery pack includes a battery pack, the battery packs may be electrically connected in series, electrically connected in parallel, or electrically connected in a combination of series and parallel connections. Alternatively, when each battery pack includes a single battery, the batteries may be electrically connected in series, electrically connected in parallel, or electrically connected in a combination of series and parallel connections.

[0186] Next, an example of a vehicle according to an embodiment will be described with reference to the drawings.

[0187] FIG. 13 is a partially see-through view that diagrammatically illustrates an example of a vehicle.

[0188] A vehicle 400 shown in Fig. 13 includes a vehicle body 40 and a battery pack 300 according to the fifth embodiment. In the example shown in Fig. 13, the vehicle 400 is a four-wheeled automobile.

[0189] The vehicle 400 may be equipped with a plurality of battery packs 300. In this case, the batteries (e.g., single cells or assembled batteries) included in the battery pack 300 may be connected in series, in parallel, or in a combination of series and parallel connections.

[0190] 13 illustrates an example in which the battery pack 300 is mounted in an engine room located in the front of the vehicle body 40. As described above, the battery pack 300 may be mounted, for example, in the rear of the vehicle body 40 or under a seat. This battery pack 300 can be used as a power source for the vehicle 400. In addition, this battery pack 300 can recover regenerative energy for the motive power of the vehicle 400.

[0191] Next, an embodiment of the vehicle according to the embodiment will be described with reference to FIG.

[0192] Fig. 14 is a diagram illustrating an example of a control system for an electrical system in a vehicle. The vehicle 400 illustrated in Fig. 14 is an electric vehicle.

[0193] The vehicle 400 shown in FIG. 14 comprises a vehicle body 40, a vehicle power supply 41, a vehicle ECU (ECU: Electric Control Unit) 42 which is a higher-level control device of the vehicle power supply 41, an external terminal (terminal for connecting to an external power supply) 43, an inverter 44, and a drive motor 45.

[0194] The vehicle 400 has a vehicle power supply 41 mounted, for example, in an engine compartment, the rear of the vehicle body, or under a seat. Note that in the vehicle 400 shown in Fig. 14, the mounting location of the vehicle power supply 41 is shown diagrammatically.

[0195] The vehicle power supply 41 includes a plurality of (eg, three) battery packs 300a, 300b, and 300c, a battery management unit (BMU) 411, and a communication bus 412.

[0196] The battery pack 300a includes an assembled battery 200a and an assembled battery monitoring device 301a (for example, VTM: Voltage Temperature Monitoring). The battery pack 300b includes an assembled battery 200b and an assembled battery monitoring device 301b. The battery pack 300c includes an assembled battery 200c and an assembled battery monitoring device 301c. The battery packs 300a to 300c are battery packs similar to the above-mentioned battery pack 300, and the assembled batteries 200a to 200c are assembled batteries similar to the above-mentioned battery pack 200. The assembled batteries 200a to 200c are electrically connected in series. The battery packs 300a, 300b, and 300c can be removed independently and replaced with another battery pack 300.

[0197] Each of the assembled batteries 200a to 200c includes a plurality of unit cells connected in series. At least one of the plurality of unit cells is the secondary battery according to the third embodiment. Each of the assembled batteries 200a to 200c is charged and discharged via a positive terminal 413 and a negative terminal 414.

[0198] The battery management device 411 communicates with the assembled battery monitoring devices 301a to 301c, and collects information on the voltage, temperature, and the like of each of the cells 100 included in the assembled batteries 200a to 200c included in the vehicle power supply 41. In this way, the battery management device 411 collects information on the maintenance of the vehicle power supply 41.

[0199] The battery management unit 411 and the assembled battery monitoring units 301a to 301c are connected via a communication bus 412. In the communication bus 412, one set of communication lines is shared by a plurality of nodes (the battery management unit 411 and one or more assembled battery monitoring units 301a to 301c). The communication bus 412 is a communication bus configured based on, for example, the CAN (Control Area Network) standard.

[0200] The battery pack monitoring devices 301a to 301c measure the voltage and temperature of each of the cells constituting the battery packs 200a to 200c based on commands communicated from the battery management device 411. However, the temperature can be measured at only a few points per battery pack, and it is not necessary to measure the temperatures of all the cells.

[0201] The vehicle power supply 41 may also have an electromagnetic contactor (for example, a switch device 415 shown in FIG. 14) that switches between the presence and absence of an electrical connection between the positive terminal 413 and the negative terminal 414. The switch device 415 includes a pre-charge switch (not shown) that is turned on when the assembled batteries 200a to 200c are charged, and a main switch (not shown) that is turned on when the output from the assembled batteries 200a to 200c is supplied to a load. Each of the pre-charge switch and the main switch includes a relay circuit (not shown) that is switched on or off by a signal supplied to a coil disposed in the vicinity of the switch element. The electromagnetic contactor such as the switch device 415 is controlled based on a control signal from the battery management device 411 or the vehicle ECU 42 that controls the operation of the entire vehicle 400.

[0202] The inverter 44 converts the input DC voltage into a three-phase alternating current (AC) high voltage for driving the motor. The three-phase output terminals of the inverter 44 are connected to the three-phase input terminals of the drive motor 45. The inverter 44 is controlled based on a control signal from the battery management device 411 or the vehicle ECU 42 for controlling the operation of the entire vehicle. By controlling the inverter 44, the output voltage from the inverter 44 is adjusted.

[0203] The drive motor 45 rotates by electric power supplied from the inverter 44. A driving force generated by the rotation of the drive motor 45 is transmitted to the axles and drive wheels W via, for example, a differential gear unit.

[0204] Although not shown, the vehicle 400 is also equipped with a regenerative braking mechanism (regenerator). The regenerative braking mechanism rotates the drive motor 45 when the vehicle 400 is braked, and converts kinetic energy into regenerative energy as electrical energy. The regenerative energy recovered by the regenerative braking mechanism is input to the inverter 44 and converted into a direct current. The converted direct current is input to the vehicle power source 41.

[0205] One terminal of a connection line L1 is connected to the negative terminal 414 of the vehicle power supply 41. The other terminal of the connection line L1 is connected to a negative input terminal 417 of the inverter 44. A current detection unit (current detection circuit) 416 in the battery management device 411 is provided between the negative terminal 414 and the negative input terminal 417 on the connection line L1.

[0206] One terminal of a connection line L2 is connected to the positive electrode terminal 413 of the vehicle power supply 41. The other terminal of the connection line L2 is connected to a positive electrode input terminal 418 of the inverter 44. A switch device 415 is provided in the connection line L2 between the positive electrode terminal 413 and the positive electrode input terminal 418.

[0207] The external terminal 43 is connected to the battery management unit 411. The external terminal 43 can be connected to, for example, an external power source.

[0208] In response to operational inputs from the driver or the like, the vehicle ECU 42 coordinates with other management devices and control devices including the battery management device 411 to control the vehicle power supply 41, the switch device 415, the inverter 44, etc. Through the coordinated control of the vehicle ECU 42, etc., the output of power from the vehicle power supply 41 and the charging of the vehicle power supply 41 are controlled, and the entire vehicle 400 is managed. Data relating to the maintenance of the vehicle power supply 41, such as the remaining capacity of the vehicle power supply 41, is transferred between the battery management device 411 and the vehicle ECU 42 via a communication line.

[0209] The vehicle according to the sixth embodiment is equipped with the battery pack according to the fifth embodiment, and therefore has high performance and high reliability. EXAMPLES

[0210] Examples will be described below.

[0211] Example 1 <Synthesis of active materials> First, commercially available oxide reagents Nb2O5 and TiO2 were prepared. These powders were weighed so that the molar ratio of Nb / Ti was 1.0. Furthermore, Na2SO4 was added so that the molar ratio of Nb / S was 1:0.1. These were mixed using a ball mill for 1 hour. The obtained mixture was placed in an electric furnace and subjected to pre-firing at a temperature of 1000°C for 12 hours. The powder after the pre-firing was placed again in a ball mill and mixed for 1 hour. The mixture was placed again in an electric furnace and the first main firing was performed at a temperature of 1100°C for 5 hours. After cooling to room temperature, crushing was performed using a ball mill for 1 hour, and the second main firing was performed at a temperature of 1100°C for 5 hours. The removed powder was strongly crushed using a hammer mill and a roller compactor, and crushed in a wet ball mill for 3 hours. The obtained powder was placed in an electric furnace whose furnace temperature had been previously raised to 1100°C and reheated for 1 hour. Thereafter, the powder was quickly removed from the electric furnace and cooled in liquid nitrogen, thus obtaining an active material powder according to Example 1.

[0212] <Negative electrode production> Acetylene black (AB) as a conductive agent was mixed in a ratio of 10 parts by weight per 100 parts by weight of the active material powder. This mixture was dispersed in NMP (N-methyl-2-pyrrolidone), and polyvinylidene fluoride (PVdF) as a binder was mixed in a ratio of 10 parts by weight per 100 parts by weight of the active material powder to prepare an electrode slurry. This slurry was applied onto a current collector made of aluminum foil, and dried to obtain an electrode in which an active material-containing layer was applied to both sides of the aluminum foil. The obtained electrode was compacted at a predetermined pressing pressure using a roll press device to obtain an electrode density of 2.3 g / cm.3 Next, the active material-containing layer was punched out to obtain a negative electrode having an electrode area of ​​100 mm x 80 mm.

[0213] <Positive electrode production> Instead of the active material powder obtained by synthesis, LiNi 0.5 Co 0.2 Mn 0.3 O2 was used as the positive electrode active material, and the electrode was prepared in the same mixture ratio with AB and PVdF as the negative electrode, and the electrode density was 2.6 g / cm 3 Next, the active material-containing layer was punched out to obtain a positive electrode having an electrode area of ​​100 mm x 80 mm.

[0214] <Battery construction> Next, the previously prepared positive electrode, one separator, negative electrode, and another separator were repeatedly stacked in this order to obtain a laminate, which was then hot-pressed at 90°C to produce an electrode group with a thickness of 2.0 mm.

[0215] Positive and negative electrode terminals were joined to the obtained electrode group. Next, the electrode group was stored in a pack made of a laminate film and vacuum dried at 80° C. for 24 hours. The laminate film was composed of a polypropylene layer formed on both sides of an aluminum foil with a thickness of 40 μm, and had a total thickness of 0.1 mm.

[0216] A liquid nonaqueous electrolyte was poured into the laminate film pack containing the electrode group as described above. The liquid nonaqueous electrolyte was a solution in which LiPF6 was dissolved at a concentration of 1M as an electrolyte salt in a mixed solution in which propylene carbonate (PC) and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1. The pack was then completely sealed by heat sealing. Thus, a nonaqueous electrolyte battery with a width of 110 mm, a length of 85 mm, and a thickness of 2.2 mm was produced.

[0217] The nonaqueous electrolyte battery produced was charged and discharged in the range of 25%-75% depth of charge (DOD). The charge and discharge current value was set to 0.2C (time discharge rate), and the 0.2C discharge capacity was confirmed at room temperature. The 0.2C discharge capacity value is an index of energy density. The capacity of the nonaqueous electrolyte battery produced in Example 1 was 2000mAh.

[0218] Example 2 An active material powder was synthesized in the same manner as described in Example 1, except that the amount of Na2SO4 added was changed so that the molar ratio of Nb / S was 1:0.5. A nonaqueous electrolyte battery was fabricated using this active material powder as the negative electrode.

[0219] Example 3 An active material powder was synthesized in the same manner as described in Example 1, except that the amount of Na2SO4 added was changed so that the molar ratio of Nb / S was 1:1. A nonaqueous electrolyte battery was fabricated using this active material powder as the negative electrode.

[0220] Example 4 An active material powder was synthesized in the same manner as described in Example 1, except that in addition to Na2SO4, K3PO4 was added so that the molar ratio of Nb / P was 1:0.1. A nonaqueous electrolyte battery was produced by using this active material powder in the negative electrode.

[0221] Comparative Example 1 An active material powder was synthesized in the same manner as in Example 1, except that Na2SO4 as a flux was not added, and a nonaqueous electrolyte battery was fabricated using this active material powder in the negative electrode.

[0222] Comparative Example 2 An active material powder was synthesized in the same manner as described in Example 1, except that FePO4 was added instead of Na2SO4 so that the molar ratio of Nb / P was 1:0.5. A nonaqueous electrolyte battery was produced using this active material powder as the negative electrode.

[0223] Comparative Example 3 An active material powder was synthesized in the same manner as described in Example 1, except that KCl was added instead of Na2SO4 so that the molar ratio of Nb / K was 1:0.5. A nonaqueous electrolyte battery was fabricated using this active material powder as the negative electrode.

[0224] Comparative Example 4 An active material powder was synthesized in the same manner as in Example 1, except that the temperature of the reheat treatment was changed to 1400° C., and a nonaqueous electrolyte battery was fabricated using this active material powder in the negative electrode.

[0225] <Powder X-ray diffraction measurement> For the active material powders synthesized in each example, the diffraction patterns were obtained according to the method described in the first embodiment, and analysis was performed by the Rietveld method. The crystallite diameters were also examined from the obtained diffraction lines. Table 1 shows the crystallite diameters of the active material powders according to each example.

[0226] <Measurement of necking ratio N> For the active material powders synthesized in each example, the total perimeter L of the primary particles and the total perimeter L of the primary particles excluding the necking portion were calculated using the image analysis tool ImageJ according to the method described in the first embodiment. cl Relationship between (LL cl The necking ratio N, expressed as n / L, was measured. Assuming that the particle cross section of the active material was a perfect circle, the average particle diameter D was calculated from the total number of particles n observed and the total perimeter L (D=L / nπ). The results are shown in Table 1.

[0227] <Confirmation of impurity elements> For the active material powders synthesized in each example, the presence or absence of impurities in the necking portion of the grain boundary of the necking portion was confirmed according to the method described in the first embodiment. The results are shown in Table 1.

[0228] <Battery performance evaluation> The nonaqueous electrolyte batteries prepared in Examples 1-4 and Comparative Examples 1-4 were discharged at 10C to obtain the discharge capacity ratio to the 0.2C capacity as an index of rapid discharge performance. In addition, in order to confirm that stable charge and discharge are possible, each nonaqueous electrolyte battery was repeatedly charged and discharged 5000 times (one cycle is one charge and one discharge), and the discharge capacity retention rate after 5000 cycles was examined. The repeated charge and discharge were performed at 45°C with a current value of 10C (hourly discharge rate) during charging and a current value of 10C (hourly discharge rate) during discharging in the range of 25%-75% depth of charge (DOD). In order to confirm the discharge capacity retention rate after 5000 times, the battery was charged and discharged again at 0.2C (hourly discharge rate), and the discharge capacity after 5000 times was divided by the initial discharge capacity and multiplied by 100 to calculate the capacity retention rate (%) when the initial discharge capacity was 100%. This capacity retention rate is an index of long life performance. The above results are summarized in Table 1.

[0229] [Table 1]

[0230] As shown in Table 1, the necking ratio N of the active materials synthesized in Examples 1-4 was in the range of more than 0.1 and not more than 0.6. In contrast, the ratio N of Comparative Example 1 was 0.1, and the ratio N of Comparative Examples 2-4 was more than 0.6. The nonaqueous electrolyte batteries using the active materials according to Examples 1-4 in the negative electrodes exhibited higher rapid discharge performance (10C / 0.2C capacity ratio) and cycle life performance (discharge capacity retention rate after 5000 cycles) than the batteries using the active materials according to Comparative Examples 1-4.

[0231] According to at least one of the embodiments described above, an active material is provided. The active material includes secondary particles including a plurality of primary particles including a niobium-containing oxide. The secondary particles include adjacent portions where the primary particles are adjacent to each other and necked portions where the primary particles are joined to each other. The total perimeter L of the primary particles and the sum of the perimeters of the primary particles excluding the necked portions L cl That is, 0.1<(LL cl) / L≦0.6 is satisfied. With this active material, it is possible to provide an electrode capable of realizing a secondary battery capable of exhibiting high output performance and excellent life performance, a secondary battery and battery pack capable of exhibiting high output performance and excellent life performance, and a vehicle equipped with this battery pack.

[0232] Although some embodiments of the present invention have been described, these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. These embodiments and their modifications are included in the scope and spirit of the invention, and are included in the scope of the invention and its equivalents described in the claims.

[0233] Several embodiments according to the present invention will be described below. [1] A niobium-containing oxide-containing secondary particle, The secondary particles include adjacent portions where the primary particles are adjacent to each other and necking portions where the primary particles are joined to each other, The total perimeter L of the primary particles and the sum L of the perimeter of the primary particles excluding the necking portion cl That is, 0.1<(LL cl ) / L≦0.6. [2] The active material according to [1], wherein the crystallite size of the niobium-containing oxide is 10 nm or more and 300 nm or less, the average particle size of the primary particles is within the range of 0.5 μm or more and 3 μm or less, and grain boundaries containing niobium and one or more elements selected from the group consisting of P, K, and Fe are formed between the crystallites, similar to those of the parent phase. [3] The active material according to [2], wherein the concentration of the element in the grain boundary is 20% or more higher than the concentration in the parent phase. [4] An electrode comprising the active material according to any one of [1] to [3]. [5] The electrode according to [4], wherein the electrode includes an active material-containing layer that contains the active material. [6] A positive electrode; a negative electrode including a negative electrode active material; and an electrolyte, the negative electrode active material includes secondary particles including a plurality of primary particles including a niobium-containing oxide, the secondary particles including a first adjacent portion where the primary particles are adjacent to each other and a second adjacent portion where the primary particles are in contact with each other via an interface; The total perimeter L of the primary particles and the sum L of the perimeters of the primary particles excluding the second adjacent portion cl That is, 0.1≦(LL cl ) / L≦0.6. [7] A battery pack comprising the secondary battery described in [6]. [8] An external terminal for supplying current; Protection circuit and The battery pack according to [7], further comprising: [9] A battery comprising a plurality of the secondary batteries, The battery pack according to [7] or [8], wherein the secondary batteries are electrically connected in series, in parallel, or in a combination of series and parallel.

[10] A vehicle equipped with a battery pack described in any one of [7] to [9].

[11] A vehicle as described in

[10] , including a mechanism for converting kinetic energy of the vehicle into regenerative energy. [Explanation of symbols]

[0234] Reference Signs List 1...electrode group, 2...exterior member, 3...negative electrode, 3a...negative electrode current collector, 3b...negative electrode active material-containing layer, 3c...negative electrode current collector tab, 4...separator, 5...positive electrode, 5a...positive electrode current collector, 5b...positive electrode active material-containing layer, 6...negative electrode terminal, 7...positive electrode terminal, 11...primary particle, 12...secondary particle, 13...necking portion, 14...isolated particle, 15...periphery, 16...boundary, 21...bus bar, 22...positive Positive electrode lead, 23... negative electrode lead, 24... adhesive tape, 31... container, 32... lid, 33... protective sheet, 34... printed wiring board, 35... wiring, 40... vehicle body, 41... vehicle power source, 42... electrical control device, 43... external terminal, 44... inverter, 45... drive motor, 100... secondary battery, 200... battery pack, 200a... battery pack, 200b... battery pack, 200c ...battery pack, 300...battery pack, 300a...battery pack, 300b...battery pack, 300c...battery pack, 301a...battery pack monitoring device, 301b...battery pack monitoring device, 301c...battery pack monitoring device, 342...positive connector, 343...negative connector, 345...thermistor, 346...protection circuit, 342a...wiring, 343a...wiring, 350...external terminal for energization, 352...positive terminal, 353...negative terminal, 348a...positive wiring, 348b...negative wiring, 400...vehicle, 411...battery management device, 412...communication bus, 413...positive terminal, 414...negative terminal, 415...switch device, 416...current detection unit, 417...negative input terminal, 418...positive input terminal, L1...connection line, L2...connection line, W...drive wheel.

Claims

1. secondary particles including a plurality of primary particles including a niobium-containing oxide; The secondary particles include adjacent portions where the primary particles are adjacent to each other and necking portions where the primary particles are joined to each other, The total perimeter L of the primary particles and the sum L of the perimeters of the primary particles excluding the necking portion cl That is, 0.1 < (L - L cl ) / L≦0.

6.

2. 2. The active material according to claim 1, wherein the crystallite size of the niobium-containing oxide is 10 nm or more and 300 nm or less, the average particle size of the primary particles is within the range of 0.5 μm or more and 3 μm or less, and grain boundaries containing niobium and one or more elements selected from the group consisting of P, K, and Fe are formed between the crystallites, similar to those of the parent phase.

3. 3. The active material according to claim 2, wherein the concentration of the element in the grain boundary is at least 20% higher than the concentration in the parent phase.

4. An electrode comprising the active material according to any one of claims 1 to 3.

5. The electrode according to claim 4 , wherein the electrode comprises an active material-containing layer that contains the active material.

6. A positive electrode and a negative electrode including a negative electrode active material; and an electrolyte, the negative electrode active material includes secondary particles including a plurality of primary particles including a niobium-containing oxide, the secondary particles including a first adjacent portion where the primary particles are adjacent to each other and a second adjacent portion where the primary particles are in contact with each other via an interface; The total perimeter L of the primary particle and the sum L of the perimeters of the primary particle excluding the second adjacent portion cl That is, 0.1≦(L−L cl ) / L≦0.

6.

7. A battery pack comprising the secondary battery according to claim 6.

8. An external terminal for supplying electricity; Protection circuit and The battery pack of claim 7 further comprising:

9. A battery comprising a plurality of the secondary batteries, The battery pack according to claim 7 , wherein the secondary batteries are electrically connected in series, in parallel, or in a combination of series and parallel.

10. A vehicle equipped with the battery pack according to claim 7.

11. The vehicle according to claim 10, further comprising a mechanism for converting kinetic energy of the vehicle into regenerative energy.

Citation Information

Patent Citations

  • Electrode, secondary battery, battery pack, and vehicle

    JP2019169348A

  • Active material, active material composite material, electrode, secondary battery, battery pack, and vehicle

    JP2019169399A

  • Active material, electrode, secondary battery, battery pack, and vehicle

    JP2020047374A

  • Electrode, battery, and battery pack

    JP2021150059A

  • Active material, electrode, secondary battery, battery pack, and vehicle

    JP2023135184A